Використання штучного інтелекту в ігрових застосунках - Обидало, О. С.; Пономарьова, С. В. (ХНУРЕ, 2025)
The paper discusses the use of artificial intelligence in gaming applications and ІТs impact on the development of the gaming industry. The main areas of AI use are identified, including the management of non-game characters, balancing game complexІТy, and optimization of physical simulations. Machine learning methods are described, including reinforcement learning and supervised learning, which allow to adapt the gameplay to the player. The role of AI in the generation of game worlds is considered, which helps to accelerate content development. The advantages of using AI to create realistic and dynamic gaming environments are identified.
Keywords: ігровий застосунок; gaming applications